The problem of the archaeological record before 1000 AP and the ceramic incised/engraved in the area of the Salado River (plain of Santiago del Estero, Argentina) El problema del registro arqueológico anterior al 1000 AP y la cerámica incisa/grabada en la zona del río Salado (llanura de Santiago del Estero, Argentina) - Taboada, Constanza (2020)
This paper seeks to make visible and problematize the eventuality of archaeological records attributable to the first millennium known for the Salado River area (Santiago del Estero, Argentina), as well as the problems that arise from the ceramic classifications related to it. For this, it reevaluates data available and the ways of building them throughout the history of local archeology. As a result, the homogenization that has acted on the variability of incised ceramics or local engravings is evident, as well as the problems and potentials of contextual and chronological attribution. The analysis shows a clear installation for the boundary between the first and second millennium and the possibility of a previous installation already associated with mounds and not registered at that time in the area of the Dulce River. Finally, some working hypotheses are postulated to guide new observations. They suggest that a sum of factors of different kinds (data generation modes, site-forming factors, environmental dynamics, lifestyles, etc.) could act generating a very low visibility and registration of sites / evidence prior to 1000 BP in an area where the installation could - for environmental and cultural reasons to deepen - be of low density